Extracellular vesicles derived from M1 macrophages enhance rat midpalatal suture expansion by promoting initial bone turnover and inflammation - Yi Liu; Yuan Zhong; Bowen Zheng; Yi Liu (Progress in Orthodontics, 2023)
Abstract Background Midpalatal suture (MPS) expansion can be affected by many factors, and researchers have attempted to regulate the initial inflammatory stage of expansion to optimize clinical outcomes and their underlying mechanisms. This study aimed to investigate the potential effects and mechanisms of M1 macrophage small extracellular vesicles during rat MPS expansion. Materials and methods RAW264.7 cells were induced to M1 or M2 polarization and, small extracellular vesicles were isolated from the polarized macrophages. Male Sprague–Dawley rats (6–7 weeks) were administered 70 ± 5 g expansion force devices for 7 days. Rats with expanders without force served as controls. M1/M2 small extracellular vesicles were injected into the MPS region (50 µg/day) in the M1 and M2 small extracellular vesicle-assisted groups, while 0.9% saline was injected into the expansion-only group. Suture width, bone mass, and morphological changes in the region of interest (ROI) were examined. Results The M1 small extracellular vesicle-assisted group showed a significantly increased MPS suture width in vivo (P < 0.001), and less bone mass was observed in the ROI (P < 0.05). Histological examination showed that the M1 small extracellular vesicle-assisted group exhibited a wider palatal area and obvious fibrous tissue rearrangement. The expression of RANKL and the number of osteoclasts were increased (P < 0.01) in the bony edges, and the p65 protein expression was significantly higher (P < 0.001). Conclusions M1 macrophage-derived small extracellular vesicles have a positive effect in MPS expansion and increase p65 protein content and RANKL expression, thus promoting bone turnover. This study may contribute to the clinical application of small extracellular vesicles in the expansion of the palatal suture.